Translator’s Frequent Lexis Store and Dictionary Use as Factors in SLT Comprehension and Translation Speed – A Comparative Study of Professional, Paraprofessional and Novice Translators - Ronowicz, Eddie; Hehir, Joanna; Kaimi, Toshihiro; Kojima, Keiko; Lee, Deok-Shin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article examines empirical evidence on the use of translational aids from TAP studies over the last two decades and describes a think aloud protocol (TAP) study designed to verify some of these claims. Following a description of methodology used, the results of the study are presented and discussed. Basing on experience gained from the study, a number of methodological issues are then discussed: the use of students as subjects in TAP studies, the use of postgraduate students as co-investigators, as well as advantages and shortcomings of TAP methodology.